Art-biografie Andrzeja Wróblewskiego - Nowicka, Daria (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The essay concerns the ways of reading and understanding the biographies of Andrzej Wróblewski, one of the prominent representatives of modernist and post-war painters. One special case is the art-biography project showing the need to reinterpret the author’s current biographical facts. The reading of texts by Jan Michalski, Magdalena Ziółkowska, Wojciech Grzybała and Andy Rottenberg shows this mechanism – expanding the constellations of Andrzej Wróblewski.